If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8d + 18 + -1d = d Reorder the terms: 18 + 8d + -1d = d Combine like terms: 8d + -1d = 7d 18 + 7d = d Solving 18 + 7d = d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-1d' to each side of the equation. 18 + 7d + -1d = d + -1d Combine like terms: 7d + -1d = 6d 18 + 6d = d + -1d Combine like terms: d + -1d = 0 18 + 6d = 0 Add '-18' to each side of the equation. 18 + -18 + 6d = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 6d = 0 + -18 6d = 0 + -18 Combine like terms: 0 + -18 = -18 6d = -18 Divide each side by '6'. d = -3 Simplifying d = -3
| 65=35+a(3.4) | | 32+(3x)=12-x | | ny-6+y+8=42 | | 3(2+x)=10 | | 2.7b-9.8=15.2 | | -7-5/6x=18 | | (3/4)/(1/2) | | 4y+y+1=2z+13 | | A=9x+3xy | | 10b+10=8b-8 | | 15X+22=8X-11 | | 1=1/2x-3/4x | | 17=4x-16 | | 6X=17+1 | | 3k+4=2k | | 1-5n=1-5n | | 12+8x=5(x+8) | | 6X=17+11 | | 12y=3y+3z | | 3/76/x | | (2x-3)(4x+2)=0 | | -2f-4=-f | | 5(x+1)=2(3x-4) | | 43=2x-3 | | -8(6w-7)=50 | | 7=6x-86 | | 13=44 | | 7=5x-46 | | 2x+20+4x=0 | | p/3=2/6 | | 9-3r=-4r | | 1m+3=9+3m |